Overview Of Elderly Knowledge About Rheumatoid Arthritis In Barusjahe District Puskesmas Karo 2021 - Indra Hizkia; Lilis Novitarum; Mestiana Br Karo (Institute of Computer Science (IOCS), 2021)
Elderly is an age that has a greater likelihood of experiencing autoimmune, this is based on the statement that the older you get or the older you are, the more likely you are to experience autoimmune. Rheumatoid Arthritis (RA) is an autoimmune and immune system disease that causes chronic inflammation of the joints. This research purposed to describe the knowledge of the elderly about Rheumatoid arthritis in the Barusjahe Health Center Work Area, Karo Regency in 2021. This research uses descriptive research with the sampling technique in this study using purposive sampling. The number of respondents are 72 people. The research instrument is a questionnaire on the level of knowledge about Rheumatoid Arthritis with 25 questions. The results of this study are most of the knowledge level of the elderly about Rheumatoid Arhritis obtained in the category of sufficient knowledge level of 47.2%, 27.8% less, and 25% good. The conclusion is that the level of knowledge of the elderly about Rheumatoid Arthritis at the Barusjahe Health Center in 2021 is mostly good enough, it is hoped that health cadres can provide further information about rheumatoid arthritis so that they can increase the knowledge of the elderly to be good and improve the health status of the elderly